2022
DOI: 10.3390/ijms23147783
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of the pIgR Gene from the Antarctic Teleost Trematomus bernacchii Reveals Distinctive Features of Cold-Adapted Notothenioidei

Abstract: The IgM and IgT classes were previously identified and characterized in the Antarctic teleost Trematomus bernacchii, a species belonging to the Perciform suborder Notothenoidei. Herein, we characterized the gene encoding the polymeric immunoglobulin receptor (pIgR) in the same species and compared it to the pIgR of multiple teleost species belonging to five perciform suborders, including 11 Antarctic and 1 non-Antarctic (Cottoperca gobio) notothenioid species, the latter living in the less-cold peri-Antarctic … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 84 publications
(120 reference statements)
0
2
0
Order By: Relevance
“…Amino acid changes near or within the functional domains of immune system proteins are one of the main molecular mechanisms underlying adaptations to environmental pathogens [4,120]. Mutations giving rise to habitat-specific functional adaptive variation in immune system genes (IGHM, IGHE IGH, CD14, CD40, CD80, IFNAR2, LY96, TAB 1, TICAM1, TLR4, MDA5, chicken type lysozyme, and pIGR) have been observed in different vertebrates and can happen through insertions (e.g., MUC7 in primates) or gene duplications [121][122][123][124][125][126][127][128]. For the pIGR specifically, research suggests that the observed mutations occurred through an insertion of transposable elements [127].…”
Section: Environmental Pathogensmentioning
confidence: 99%
See 1 more Smart Citation
“…Amino acid changes near or within the functional domains of immune system proteins are one of the main molecular mechanisms underlying adaptations to environmental pathogens [4,120]. Mutations giving rise to habitat-specific functional adaptive variation in immune system genes (IGHM, IGHE IGH, CD14, CD40, CD80, IFNAR2, LY96, TAB 1, TICAM1, TLR4, MDA5, chicken type lysozyme, and pIGR) have been observed in different vertebrates and can happen through insertions (e.g., MUC7 in primates) or gene duplications [121][122][123][124][125][126][127][128]. For the pIGR specifically, research suggests that the observed mutations occurred through an insertion of transposable elements [127].…”
Section: Environmental Pathogensmentioning
confidence: 99%
“…However, there is a gap in our knowledge of how epigenetic variation arises. Transposon activity has also been proposed as a mechanism involved in adaptive variation within regulatory mechanisms [77,127]. Altogether, these developments suggest that there could be mechanisms in place that leads to an increased occurrence of adaptive variation within specific regions of the genome.…”
Section: Future Researchmentioning
confidence: 99%